Plasmodesmata “in Communicado” - Maule, Andy; Faulkner, Christine; Benitez-Alfonso, Yoselin (Frontiers in Plant Science, 2012)
Cell-to-cell communication is fundamental to multicellular life. For this to occur effectively there must be pathways and dynamic networks for communication. These might depend upon electrical or chemical signals or the mass transfer of molecules between adjacent cells. Molecular communication occurs either via an extra-cellular pathway or through physical structures, called Plasmodesmata, that connect the cytoplasm of neighbouring cells. Plasmodesmata bridge the rigid physical barrier presented by the cell wall to extend the symplasm from single cells to tissue domains that have functional importance for tissue growth, development and defence. Although recent years have seen advances in our knowledge of the physical nature of PD, the trafficked molecules, and of the wider processes they affect, our knowledge of PD structure and function is still relatively rudimentary. This article will consider the technical/experimental difficulties hindering PD research and suggest priorities in the future research effort that might advance the field at a significantly faster rate.